The Effect of the Covid-19 Pandemic on the Compliance Level of Annual SPT Reporting for Individual Taxpayers at the Pondok Aren Tax Office, South Tangerang City - Ambarwati Ambarwati; Indra Sumarna Sobari; Rudi Kristanto (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
The Covid 19 pandemic in Indonesia began in early 2020 which caused changes in the economy to become unstable and the wheels of business were hampered or some even stopped their activities.The Covid-19 pandemic has caused open unemployment (TPT) and poverty, the impact experienced by all taxpayers throughout the country is at least enough to make activities in this country not conducive.In order to realize the national economic recovery due to the impact of the Covid-19 pandemic which has experienced a very significant decline and low tax revenues are consequences that the government must accept. Through the Ministry of Finance issued several incentive and relaxation policies in the field of taxation for taxpayers affected by the Covid-19 pandemic.Government policy refers to the efforts made to attract investors in order to encourage economic activity, namely by providing tax incentives and relaxation., with the government policy of the Directorate General of Taxes (DGT) of the Ministry of Finance providing relaxation in the form of simplifying the submission of documents for completing annual notification letters or SPT, in Covid-19 pandemic conditions. This relaxation is given to corporate taxpayers and individual taxpayers.This study is intended to determine whether there is an effect of incentives and relaxation as well as an understanding of tax regulations, the quantitative method used in this study is based on tax rates and the principle of justice for mandatory compliance, during the Covid 19 pandemic, with the level of compliance in reporting the Annual Tax Return of Individual Taxpayers. Utilization of Information Technology has a significant effect on taxpayer compliance.